The Kiai’s Cultural Strategy in Shaping the Religious Culture of the Community of Temboro Magetan Village, East Java - Arifin, Zainal; Maragustam, Maragustam; Muqowim, Muqowim; 'Aziz, Hafidh (IAIN Samarinda, 2021)
Religious culture in the village of Temboro, which made it is known as